Phylogenetic Analysis of H7N9 Avian Influenza Virus Based on a Novel Mathematical Descriptor. (15th June 2014) - Bai, Yusheng; Ma, Tingting; Yao, Yuhua; Dai, Qi; He, Ping-an
Abstract : A new mathematical descriptor was proposed based on 3D graphical representation. Using the method, we construct the phylogenetic trees of nine proteins of H7N9 influenza virus to analyze the originated source of H7N9. The results show that the evolution route of H7N9 avian influenza is from America through Europe to Asia. Furthermore, two samples collected from environment in Nanjing and Zhejiang and one sample collected from chicken are the sources of H7N9 influenza virus that infected human in China.